Prediction of MACE by Angiographic Perfusion Score (APS) in Risk Stratification following Percutaneous Coronary Stenting in STEMI without Thrombolytic Therapy - Md Iqbal, Khaled; Ahsan, Syed Ali; Rahman, Md Mukhlesur; Chowdhury, MSI Tipu; Ahmed, Khurshed; Parvin, Tanjima; Md Jamil, Abu Baqar; Khaled, Md Fakhrul Islam; Malla, Sabindra Bhupal; Gachchhadar, Pritam Kumar; Mandal, MRM (University Heart Journal, 2019)
Background: ST-elevation myocardial infarction (STEMI) is a major cause of mortality worldwide. PCI remain gold standard management of STEMI. An Angiographic Perfusion Score (APS) is a combination of TIMI Flow Grades (TFG) and myocardial perfusion (TMPG) grades before and after PCI. So it can accurately measure both epicardailand myocardial perfusion and predict major adverse cardiac events (MACE). The aim of the study is to evaluate the association of APS for determining the short term clinical outcomes after PCI in ST-segment elevation myocardial infarction without thrombolytic therapy. Methodology: This cross sectional observational study carried out among adult patients presenting STsegment elevation myocardial infarction without thrombolytic pretreatment to the cardiology department of BSMMU who underwent Percutaneous Coronary Intervention and met inclusion and exclusion criteria. This study was conducted from April 2017 to March 2018. After informed written consent data collection was carried out by using a data sheet. Calculated sample size of the study was 205. Angiogram was done by SIEMENS AXOM ARTIS machine, CD Analysis to see TFG & TMPG for calculation of APS was done by two specialist observer (Professor, Associate or Assistant Professor) MACE was observed within 30 days. Chi square test was done to see the association of APS with MACE by Statistical Package for Social Science program 20 version of computer on the basis of different variables. Results: MACE distribution of the study patients revealed that only 7.8% of the patients had MACE whereas 92.2% of the patients had no MACE among 205 patient APS score with MACE distribution of the study patients revealed that 9.3% patient of partial perfusion group and 44.4% patient of failed perfusion group had MACE but there were no major adverse cardiac event in full perfusion group of patient. The difference were statistically highly significant (p<0.05) among three groups but there were no differences in the baseline characteristics of those who had full, partial or failed perfusion of APS. Conclusion: APS which combines TFG with TMPG before and after PCI is a better discriminator of 30 day MACE than TMPG or TFG alone taken only after PCI. It can identify high risk patients who need implementation of early invasive strategies. We conclude that APS is a better predictor of MACE to take care of patient more accurately. University Heart Journal Vol. 15, No. 1, Jan 2019; 16-21